2013
DOI: 10.1210/jc.2013-2454
|View full text |Cite
|
Sign up to set email alerts
|

Associations Between Ethnicity, Body Composition, and Bone Mineral Density in a Southeast Asian Population

Abstract: Lower peak BMD in Chinese men may partly explain the higher fracture incidence in this ethnic group. Further studies are needed to elucidate the reasons for these ethnic differences in bone accumulation.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

7
11
0

Year Published

2014
2014
2021
2021

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 22 publications
(18 citation statements)
references
References 46 publications
7
11
0
Order By: Relevance
“…Our findings of a positive association between lean mass and BMD are in keeping with those of Amarendra et al (27) in their study of AI men, Chantler et al (7) in BA women, and others (33). This is the first report of the significant contribution of lean mass to BMD in black South African men.…”
Section: Discussionsupporting
confidence: 92%
“…Our findings of a positive association between lean mass and BMD are in keeping with those of Amarendra et al (27) in their study of AI men, Chantler et al (7) in BA women, and others (33). This is the first report of the significant contribution of lean mass to BMD in black South African men.…”
Section: Discussionsupporting
confidence: 92%
“…The protective effect of high body mass index on BMD is well known [ 30 , 31 , 32 ]. However, studies have shown conflicting results regarding the correlation between body fat and BMD [ 19 , 20 , 21 , 23 , 24 , 25 ]. Recent studies have also shown that there are biologic and metabolic differences between the SAT and visceral adipose tissue (VAT) present in the abdominal cavity; VAT adipocytes are more metabolically active, sensitive to lipolysis, and resistant to insulin than SAT adipocytes [ 33 ].…”
Section: Discussionmentioning
confidence: 99%
“…Although the main impact is thought to be caused by the straining force exerted by the biomechanical load on the bone, the positive correlations between the fat mass and bone density in the non-weight bearing parts of the skeleton were reported to be comparable with those found in weight-bearing parts [ 18 ]. Recently, studies have shown differential degrees of association between body fat and BMD when the body fat was divided into subcutaneous and visceral fat components; visceral fat, which is considered to be the major culprit behind the MetS, has been suggested to have an inverse relationship with BMD [ 19 , 20 , 21 ], while subcutaneous fat, a positive relationship [ 22 ], although some studies have shown neutral or inconsistent results on account of their study populations and measurement protocols [ 23 , 24 , 25 ]. Therefore, we intended to investigate the effect of 'biomechanical load on the BMD' differentially by body fat amount and by skeletal muscle mass (SMM) and that of 'abdominal obesity on the BMD' by compartmental visceral and subcutaneous fat amount.…”
Section: Introductionmentioning
confidence: 99%
“…Multiple studies within the US have shown that African Americans have the highest BMD while Caucasians have the lowest [ 9 , 10 ]. We, and others, have previously demonstrated substantial ethnic variation in hip fracture incidence and BMD in Singapore, with Chinese having the highest hip fractures rates, in both men and women [ 11 ], as well as the lowest BMD [ 12 ]. Beyond BMD, the ethnic difference in fracture risk may also be due to the differences in bone size and bone geometry, such as femoral neck size, trabecular and cortical thickness and bone volume [ 13 , 14 ].…”
Section: Introductionmentioning
confidence: 99%